Fagerstrom test for nicotine dependence vs heavy smoking index in a general population survey - Malvar A; Alonso B; Santiago-Pérez MI; Pérez-Ríos M; Hervada X; de Leon J (BMC, 2009)
Abstract Background The Fagerström Test for Nicotine Dependence (FTND) is used for assessing nicotine dependence. A shorter test derived from the FTND used for the general population is the Heavy Smoking Index (HSI) (six questions vs. two). The objective of this study is to compare the validity of the HSI versus the FTND. Methods A survey of tobacco use in the general population was carried out in the northern Spanish region of Galicia using both the FTND and the HSI to study a representative sample of 1655 daily smokers. The HSI was compared with the FTND, considered the gold standard. Measures of sensitivity, specificity and predictive values were calculated. Concordance between the tests was also established (Cohen's kappa). Results Cohen's kappa showed good agreement between measures (Kappa = 0.7); specificity values were also high (Sp = 96.2%). Sensitivity analysis in females (Se = 62.3%) did not show good agreement. Conclusions The HSI can be used as a reasonably good screening test in order to identify daily smokers with high nicotine dependence. Nevertheless, for populations or subpopulations having low nicotine dependence, such as women, the FTND is more reliable.